KONSEP RISIKO DALAM PERSPEKTIF ISLAM: STUDI HERMENEUTIK TERHADAP KARYA IBNU TAIMIYAH DAN AL-GHAZALI TENTANG KHAUF WA RAJAâ (KETAKUTAN DAN HARAPAN) - , ITSNA NURRAHMA MILDAENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Risk is an inseparable part of human life. Every individual has different attitude and behavior in facing risk. The difference is influenced by many factors, including religious factor. Islam is one of the religions in Indonesia with the biggest number of followers. Islamic values, including destiny, influence a Muslimâs attitude toward risk. This study aimed to discover and develop the concept of risk in Islamic perspective. This study was a qualitative study using hermeneutic approach. Data source in this study was a classical text in Arabic by Ibnu Taimiyah and Al-Ghazali chapter Khauf wa Rajaâ (Fear and Hope). Both are famous figures from two schools of theology in Islam. Research result discovered risk concept in Islamic perspective. This risk concept is different from general risk concept. Risk in Islamic perspective emerges because of human beingsâ position as a serf. Causative factor of risk is human beingsâ limitations. These limitations include two things, i.e. ignorance and inability. This study stated that human beings had freedom to choose. This study also showed that every human action had consequences. This meant that human had a role in determining the results of their actions. For a Muslim, religious values are a guide in attitudes and behaviors, including attitudes and behaviors toward risk